2021
DOI: 10.3390/ijerph18020610
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Work Environment to Minimize the Negative Impact of Nurse Burnout on Patient Outcomes

Abstract: Background: Burnout remains a persistent issue affecting nurses across the US health system. Limited evidence exists about the direct impact of nurse burnout on patient outcomes. This study explores the relationship between nurse burnout and mortality, failure to rescue, and length of stay, while also considering the effect of a good work environment. Methods: Cross sectional data from nurses and hospitals were used in conjunction with patient claims data. Multivariate logistic regression was used to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 64 publications
3
87
1
6
Order By: Relevance
“…The staff who possess more team resources (higher teamwork climate) and more personal resources (higher job satisfaction) are less vulnerable to burnout. Although working condition was not a significant predictor of exhaustion in this study, previous research did find that good work environments could attenuate the relationship between nurses’ burnout and patient outcomes [ 12 ]. The relationship between working condition and staff exhaustion deserves further exploration.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…The staff who possess more team resources (higher teamwork climate) and more personal resources (higher job satisfaction) are less vulnerable to burnout. Although working condition was not a significant predictor of exhaustion in this study, previous research did find that good work environments could attenuate the relationship between nurses’ burnout and patient outcomes [ 12 ]. The relationship between working condition and staff exhaustion deserves further exploration.…”
Section: Discussioncontrasting
confidence: 58%
“…Finally, we found that staff exhaustion increased during the pandemic across the board. Existing studies have shown that employee burnout is related to patient mortality and hospital stay [ 12 ]. Hence, hospitals should consider increasing the number of caregivers, giving longer rest periods, providing resting places and better protective equipment and so on to reduce employee burnout [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This narrative review of the literature and subsequent policy analysis utilizes a patient‐centric lens. While nurse staffing factors, such as nurse‐to‐patient ratios, can also affect the well‐being of nurses, 5–7 this review and analysis focuses on outcomes relative to patients rather than nurses. An overall goal of this paper is to encourage readers to review nurse staffing empirical evidence to inform their perspectives as they engage with nursing organizations, hospital organizations, and state legislatures for nurse staffing policy.…”
mentioning
confidence: 99%